2000
DOI: 10.1002/biof.5520130109
|View full text |Cite
|
Sign up to set email alerts
|

Preventive effects of drinking green tea on cancer and cardiovascular disease: Epidemiological evidence for multiple targeting prevention

Abstract: The significance of drinking green tea in prevention of two of the main lifestyle-related diseases, cancer and cardiovascular disease, was demonstrated in terms of a prospective cohort study on a total of 8,552 general residents in Saitama Prefecture, Japan. On the basis of the follow-up study, we revealed decreased relative risk of cancer incidence for those consuming over 10 cups a day, compared with those consuming below 3 cups: 0.54 (95% confidence interval, 0.22-1.34) for men, 0.57 (0.34-0.98) for women, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
239
2
5

Year Published

2004
2004
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 368 publications
(256 citation statements)
references
References 9 publications
10
239
2
5
Order By: Relevance
“…Our findings are in general agreement with those of four prospective studies which found no inverse association between green tea consumption and the risk of stomach cancer (Galanis et al, 1998;Nakachi et al, 2000;Nagao et al, 2001;Tsubono et al, 2001). The number of cases of stomach cancer was relatively large in three studies.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Our findings are in general agreement with those of four prospective studies which found no inverse association between green tea consumption and the risk of stomach cancer (Galanis et al, 1998;Nakachi et al, 2000;Nagao et al, 2001;Tsubono et al, 2001). The number of cases of stomach cancer was relatively large in three studies.…”
Section: Discussionsupporting
confidence: 93%
“…Although case -control studies (Kono et al, 1988;Yu and Hsieh, 1991;Yu et al, 1995;Ji et al, 1996;Inoue et al, 1998;Setiawan et al, 2001) have found a reduced risk of stomach cancer in association with green tea consumption, prospective studies (Galanis et al, 1998;Nakachi et al, 2000;Nagao et al, 2001;Tsubono et al, 2001) have not. A recent prospective study found that green tea had a protective effect against stomach cancer.…”
mentioning
confidence: 99%
“…With the exception of one Italian case-control study, 25 studies on tea consumption and HCC risk have been conducted exclusively in Asia (where green tea consumption is more frequent than in Europe); the results are collectively inconclusive. Two studies reported statistically significant inverse associations, 28,29 four inverse but statistically nonsignificant associations, [30][31][32][33] two null associations, 19,34 whereas three reported positive, albeit statistically nonsignificant associations. 17,25,35 A meta-analysis of these studies 9 pointed to a suggestive inverse association of tea with primary liver cancer.…”
Section: Discussionmentioning
confidence: 99%
“…However, a systematic review of eight studies on green tea reported an OR of 0?82 (95 % CI 0?69, 0?98) (68) and other individual studies on green tea have indicated chemopreventive effects (69)(70)(71)(72)(73) . From nine studies, green tea consumption is possibly related to a decreased risk of colorectal cancer, while black tea consumption possibly has no relationship with colorectal cancer based on twenty-one studies.…”
Section: Cancersmentioning
confidence: 99%